DOP82 Direct and indirect costs of inflammatory bowel disease in the biological era; 10 years of follow-up in a Danish population-based inception cohort. (25th January 2019) - Lo, B; Vind, I; Vester-Andersen, M K; Bendtsen, F; Burisch, J
Abstract: Background: Crohn's disease (CD) and ulcerative colitis (UC) carries a high burden on healthcare resources. To date, no study has assessed the combined direct and indirect cost of inflammatory bowel disease (IBD) in a population-based setting. Our aim was to assess this in a population-based inception cohort with 10 years of follow-up. Methods: All incident patients diagnosed with CD or UC between 2003 and 2004 in a well-defined Copenhagen area, were followed prospectively until 2015. Information regarding direct and indirect costs was retrieved from the Danish national registries. Data were compared with a control population matched by age, sex and municipality with a ratio of 1:20 (10259). Using multiple linear regression models, associations between the total cost and multiple variables were assessed. Results: A total of 513 (CD: 213 [42%], UC: 300 [58%]) IBD patients were included. No significant differences were found in indirect costs between CD, UC, and the control population regarding paid sick leave, unemployment benefits or loss of tax income. Costs for CD patients were significantly higher than UC regarding all direct expenditures (except for 5-ASA), but no differences were found in diagnostic expenses. The expenses for biologics were, respectively, €1.6 and 0.3 million for CD and UC. The total costs accounted for €42.6€ million. Figure 1 illustrates the distribution of all expenses; Figure 2 illustrates the total costs per patient each year. Subgroup analyses only revealed significant increased direct expenses in patients with extensive colitis (Proctitis: €2273 [1341–4092], left-sided: €3606 [2354–5311], extensive: €4093 [2313–6057], p < 0.001). Using multi-variable linear regression, no variables were significantly associated with increased total costs in CD or in UC patients. Conclusions: In this prospective population-based cohort, direct costs for IBD remain high. However, indirect costs (sick leave, unemployment and loss of tax-income etc.) did not surpass the control population. Total costs were mainly driven by hospitalisation, but over time indirect costs accounted for a higher percentage; though also decreasing over years.